Gender and Environment - World Bank (Washington, DC, 2013)
This report focuses on the nexus of environment and gender equality, defined as equality of access to and control over natural resources and development benefits; and equality of access to decision-making and representation for environmental and natural resources management process. The report provides recommendations to expand women's opportunities to own land; expand men's and women's knowledge and participation in reducing exposure to environmental hazards; strengthen gender mainstreaming efforts at the national policy level; improve women's participation at national, regional and local levels; and expand women's involvement in demand-side accountability mechanisms for environmental governance.